Investigation of Optimal pH and Temperature Regimes for Maximizing Germination and Reproductive Capacity in Pearl Millet (Pennisetum glaucum) Varieties Pusa 334 and Pusa 383 - Kumar, Amresh; Bharti, Jasmine (Journal of Discoveries in Applied and Natural Science, 2026)
Background: Pearl millet (Pennisetum glaucum) is a vital staple crop in arid and semi-arid regions, yet variety-specific germination responses to abiotic factors remain inadequately characterized. Objective: This study investigated the optimal pH and temperature regimes for maximizing germination, reproductive capacity, and early seedling growth of two commercially important pearl millet varieties, Pusa 334 and Pusa 383. Methods: Seed characters and reproductive capacity were assessed following Salisbury (1942). Germination experiments were conducted across seven pH levels (4.2–10.2) and eight temperature regimes (5–40°C). Seedling growth parameters cotyledonary leaf opening, fresh biomass, dry biomass, and plant height were monitored at 5-day intervals over 20 days. Results: Pusa 334 exhibited superior reproductive capacity (1907.22) compared to Pusa 383 (1736.46), attributed to larger seed size (3 mm diameter; 1.40 g/100 seeds) and higher seed output (1850 seeds/plant). Both varieties failed to germinate at pH 4.2, with optimal germination (>85%) and maximum seedling growth recorded at pH 7.0–8.2. Temperature optima were 20–25°C, achieving peak germination (>94%) and fastest emergence (4.01–4.40 days). Extreme temperatures (5°C and 40°C) severely inhibited germination and seedling development. Pusa 334 consistently outperformed Pusa 383 across all growth parameters under optimal conditions. Conclusion: These varieties require neutral to slightly alkaline soils and 20–25°C temperatures for optimal establishment. Findings provide critical physiological benchmarks for improving pearl millet cultivation strategies in variable environments.